(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Within the context of students’ academic achievements, the aspect of “peak-performance” among students in HEIs, still remain underexplored. Graduating with/at maximum achievement is a desired goal for any student into HEI, and can never be less important. Admittedly, what students do during school periods truly can help create the high grades border difference in respect to maintaining and achieving their initial educational goal. This study seeks to identify and distill from an academic perspective, key independent variables/factors called CSFs that are decisive and significantly impact on the ability of students in HEIs to graduate with/at maximum achievement. We gleaned a set of CSFs from the literature, then refined the list to 32 so that the final list reflects broadly 6 main CSFs that relate to HEI studentship: - Behaviour towards academics, Hard work, Organization, Peers and Socials, Skills, and Studying Style or Pattern. We then applied a Multi Attributes Decision making tool, AHP on the set of CSFs. The AHP prioritizes a subset of these CSFs as being most likely contributive variables to finishing top in university. The approach in this study is unique and provides a strategic framework for decision-making. Prospective and current students, parents, educators, academic institutions and the society at large who depend on these graduates will find the study results cardinal.